Sigmoid volvulus in pregnancy: case report and review of literature - Serafeimidis, Costas (Clin Case Rep, 2016)
Sigmoid volvulus in pregnancy is a very rare condition. Despite this, clinicians should have a high index of suspicion of this condition if they encounter a pregnant woman with symptoms suggestive of bowel obstruction. Incorrect diagnosis may be catastrophic, resulting in major complications, including fetal and maternal death.